Caldera unrest driven by CO2-induced drying of the deep hydrothermal system - R. Moretti (Nature Portfolio, 2018)
Abstract Interpreting volcanic unrest is a highly challenging and non-unique problem at calderas, since large hydrothermal systems may either hide or amplify the dynamics of buried magma(s). Here we use the exceptional ground displacement and geochemical datasets from the actively degassing Campi Flegrei caldera (Southern Italy) to show that ambiguities disappear when the thermal evolution of the deep hydrothermal system is accurately tracked. By using temperatures from the CO2-CH4 exchange of 13C and thermodynamic analysis of gas ascending in the crust, we demonstrate that after the last 1982–84 crisis the deep hydrothermal system evolved through supercritical conditions under the continuous isenthalpic inflow of hot CO2-rich gases released from the deep (~8 km) magma reservoir of regional size. This resulted in the drying of the base of the hot hydrothermal system, no more buffered along the liquid-vapour equilibrium, and excludes any shallow arrival of new magma, whose abundant steam degassing due to decompression would have restored liquid-vapour equilibrium. The consequent CO2-infiltration and progressive heating of the surrounding deforming rock volume cause the build-up of pore pressure in aquifers, and generate the striking temporal symmetry that characterizes the ongoing uplift and the post-1984 subsidence, both originated by the same but reversed deformation mechanism.